Responses of carbon, nitrogen, and phosphorus contents and stoichiometry in soil and fine roots to natural vegetation restoration in a tropical mountainous area, Southern China - Hu, Gang; Zhang, Zhonghua; Li, Lei (Frontiers in Plant Science, 2023)
The stoichiometry of key elements such as C, N, and P is an important indicator of ecosystem nutrient status and biogeochemical cycling. Nevertheless, the responses of soil and plant C:N:P stoichiometric characteristics to natural vegetation restoration remain poorly understood. In this study, we investigated C, N, and P contents and stoichiometry in soil and fine roots along vegetation restoration stages (grassland, shrubland, secondary forest, and primary forest) in a tropical mountainous area in southern China. We found that soil organic carbon, total N, C:P ratio, and N:P ratio significantly increased with vegetation restoration and significantly decreased with increasing soil depth, whereas there was no significant effect on soil total P and C:N ratio. Furthermore, vegetation restoration significantly increased the fine root N and P content and N:P ratio, whereas soil depth significantly decreased the fine root N content and increased the C:N ratio. The increasing average N:P ratio in fine roots from 17.59 to 21.45 suggested that P limitation increased with vegetation restoration. There were many significant correlations between C, N, and P contents and their ratios in soil and fine roots, indicating a reciprocal control of nutrient stoichiometric characteristics between them. These results contribute to our understanding of changes in soil and plant nutrient status and biogeochemical cycling during vegetation restoration and provide valuable information for restoration and management of tropical ecosystems.